1986
DOI: 10.1002/mds.870010105
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metabolism of glucose in benign hereditary chorea

Abstract: Benign hereditary chorea (BHC) is an autosomal dominant disorder characterized by chorea of early onset with little or no progression. There is marked clinical variability in this disease with some subjects having onset in infancy and others with onset in early adulthood. In contrast to Huntington's disease (HD), there is no dementia. Computed tomography is normal in all subjects with no evidence of caudate nucleus atrophy. We present the results of positron emission tomography using 18F-2-fluorodeoxyglucose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…There is also the remote possibility that this finding is an artefact from the normalisation procedure using the thalamus as a reference area or the use of an older control group with potentially reduced brain metabolism. However, this normalisation is unlikely to have generated such an artefact in our study because similar assessments have previously been used 24. As we have described earlier, the use of an older control group was not associated with lower levels of metabolism in several studies17-20 and we have no reason to think that such an association exists.…”
Section: Discussionmentioning
confidence: 48%
“…There is also the remote possibility that this finding is an artefact from the normalisation procedure using the thalamus as a reference area or the use of an older control group with potentially reduced brain metabolism. However, this normalisation is unlikely to have generated such an artefact in our study because similar assessments have previously been used 24. As we have described earlier, the use of an older control group was not associated with lower levels of metabolism in several studies17-20 and we have no reason to think that such an association exists.…”
Section: Discussionmentioning
confidence: 48%
“…Haploinsufficiency of the TITF‐1 gene could lead to congenital deficiency of the sellar diaphragm, which is a frequent cause of an enlarged sella. FDG‐PET scan was reported to be normal in 4 patients with BHC,9 although a study performed when the molecular diagnosis was not available showed caudate hypometabolism 24. More recently reduction of technetium 99 m ethyl cysteinate dimer uptake has been demonstrated in the basal ganglia of two children studied by SPECT 25.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to HD, SCA 17, and ChAc, a relative reduction in glucose metabolism was also identified in the caudate in three patients with benign hereditary chorea (BHC) [31]. Additionally, a report of two related patients with BHC with an NKX2.1 mutation demonstrated reduced relative [ 11 C]-raclopride binding in the striatum with normal relative binding of 11-carbon-2 carbomethoxy-3-(4-[ 18 F]-fluorophenyl)tropane ([ 11 C]-CFT), a radioligand used to evaluate presynaptic dopamine transporter function [32].…”
Section: Reviewmentioning
confidence: 99%